2021
DOI: 10.1002/aoc.6262
|View full text |Cite
|
Sign up to set email alerts
|

A novel copper framework with amino tridentate N‐donor ligand as heterogeneous catalyst for ring opening of epoxides

Abstract: A novel metal-organic framework (MOF) [Cu 3 L(2,6-NDC) 2 ]Á0.5DMF (MOF-Cu-1) was synthesized by solvothermal reaction of copper nitrate trihydrate with 2,6-naphthalenedicarboxylic acid (2,6-H 2 NDC) and amino tridentate N-donor containing ligand of N 1 -(4-(1H-imidazol-1-yl)benzyl)-N 1 -(2-aminoethyl)ethane-1,2-diamine (L). MOF-Cu-1 is a three-dimensional (3D) framework with one-dimensional (1D) channels. Because of the high stability of the framework and the existence of amino functional groups, MOF-Cu-1 pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The PXRD patterns were almost maintained in these medium, except for the one in MeOH with slight disturbance. The high stability of 1 may be ascribed to the two-fold interpenetration [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PXRD patterns were almost maintained in these medium, except for the one in MeOH with slight disturbance. The high stability of 1 may be ascribed to the two-fold interpenetration [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TGA curve of 1 · x Sol in a stream of N 2 ( Figure S1, Supplementary Materials ) indicated that all lattice solvent molecules escaped over the range of ambient temperature to 100 °C, while the major structure remained stable until 150 °C. The theoretical electron number (406 electrons in the lattice voids of each cell) reported by the SQUEEZE program matched 11.3 MeOH molecules relative to each major structure [ 40 , 41 ]. Because the desolvation of the solvent molecules at room temperature was quite fast, the TGA measurement of 1 · x Sol ( Figure S1 ) could not give an accurate x value.…”
Section: Resultsmentioning
confidence: 99%
“…[20]. The experimental results indicate that both MIP and UiO are able to catalyze the ring-opening of epoxides by methanol and aniline nucleophiles under mild conditions.…”
mentioning
confidence: 89%
“…Recent innovations, including the deployment of UiO-66 functionalized with thiophene-2carboxamide [20], copper-based MOF equipped with amine-derived tridentate ligands [21], Fe3O4 nanoparticle-supported Mn (II)-azo Schiff complex [22], and Lewis acidic trifluoromethylate ionic liquids have shown potential [23]. Nevertheless, these catalysts do not come without limitations which include prolonged reaction time, the necessity for high catalyst loadings, stability concerns, and environmental implications.…”
Section: Introductionmentioning
confidence: 99%